Trauma exposure and factors associated with ICD-11 PTSD and complex PTSD in adolescence: a cross-cultural study in Japan and Lithuania. (11th July 2022) - Kazlauskas, E.; Jovarauskaite, L.; Abe, K.; Brewin, C. R.; Cloitre, M.; Daniunaite, I.; Haramaki, Y.; Hihara, S.; Kairyte, A.; Kamite, Y.; Sugimura, K.; Thoresen, S.; et al.
Abstract: Aims: Cross-cultural studies of posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) based on ICD-11 diagnostic criteria are scarce, especially in adolescence. The study aimed to evaluate the trauma exposure, prevalence and factors associated with PTSD and CPTSD in general populations of adolescents in Lithuania and Japan. Methods: The study sample comprised 1746 adolescents from Lithuania ( n = 832) and Japan ( n = 914), 49.8% female. The mean age of study participants was 15.52 (s.d. = 1.64), ranging from 12 to 18 years. ICD-11 posttraumatic disorders were assessed using the International Trauma Questionnaire – Child and Adolescent version (ITQ-CA). Results: More than half of the adolescents in a total sample (61.5%) reported exposure to at least one traumatic event in their lifetime, 80.0% in Lithuania and 44.6% in Japan, with a higher prevalence of interpersonal trauma in Lithuania and more natural disaster exposure in Japan. The prevalence of PTSD was 5.2% (95% CI 3.8–6.9%) and 2.3% (95% CI 1.4–3.5%), CPTSD 12.3% (95% CI 10.1–14.7%) and 4.1% (95% CI 2.9–5.5%) in Lithuanian and Japanese samples, respectively. Cumulative trauma exposure, female gender, loneliness and financial difficulties in family predicted both PTSD and CPTSD in the total sample. Loneliness discriminated CPTSD v . PTSD in both Lithuanian and Japanese samples. Conclusions: This cross-cultural study is among the first which reported different patterns of trauma exposure in Asian Japanese and Lithuanian adolescents in Europe. Despite differences in trauma exposure and PTSD/CPTSD prevalence, we found similar predictors in both studies, particularly the importance of cumulative trauma exposure for PTSD/CPTSD, and social interpersonal factors for the risk of CPTSD. The study supports the universality of traumatic stress reactions to adverse life experiences in adolescence across cultures and regions and highlights different levels of traumatisation of adolescents in various countries.